Research Article Trends Globally on Translation: A Bibliometric Analysis with ScienceDirect Database - Hidayati, Niswatin Nurul (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2024)
Bibliometric analysis has emerged as a powerful tool for understanding research trends in translation studies. By systematically analyzing large volumes of academic publications, bibliometric methods were able to reveal patterns and trends that might not be immediately apparent. The data for this bibliometric analysis were collected from the ScienceDirect database, https://www.sciencedirect.com/. The search focused on research articles related to translation studies published between 2015 and 2024. The keyword used was “translation” to identify relevant publications. Two main conclusions were drawn from this research. First, VOSviewer provided a global map of existing research, in this context based on the ScienceDirect database. The visualization of co-occurrences of the keyword “translation” showed that a substantial amount of research has been conducted about translation studies, such as translation related to culture, higher education, the use of questionnaires in such research, translation studies in China or France, and several other aspects. This also revealed that research on the use of Artificial Intelligence (AI) for translation had not been extensively conducted, such as the translation using ChatGPT, Google Bard AI, DeepL Translate, and others. Second, regarding authorship visualization, the visualization provided by VOSviewer helped researchers quickly identify authors or researchers who could be referenced in translation studies.